2019
DOI: 10.1111/geb.12970
|View full text |Cite
|
Sign up to set email alerts
|

Benthic habitats do show a significant latitudinal diversity gradient: A comment on Kinlock et al. (2018)

Abstract: The latitudinal diversity gradient (LDG) has been investigated for decades, with hundreds of studies focusing on different organisms, regions and habitat types. Meta‐analysis may be considered, therefore, a useful tool to explore the generality and limitations of this remarkable macroecological pattern. The first meta‐analysis exploring variations in the LDG, published by Hillebrand in 2004, revealed that the latitudinal decline in species richness seems to be indeed a general phenomenon. However, Kinlock et a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 39 publications
(77 reference statements)
0
15
0
Order By: Relevance
“…In fact, the effect size of the strength of the LDG (i.e. Fisher's transformation of the correlation between species richness and absolute latitude) was −1.17, stronger than the mean effect size estimated for other marine datasets (Hillebrand, 2004a(Hillebrand, , 2004bKinlock et al, 2018;Menegotto et al, 2019;Rivadeneira & Poore, 2020).…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…In fact, the effect size of the strength of the LDG (i.e. Fisher's transformation of the correlation between species richness and absolute latitude) was −1.17, stronger than the mean effect size estimated for other marine datasets (Hillebrand, 2004a(Hillebrand, , 2004bKinlock et al, 2018;Menegotto et al, 2019;Rivadeneira & Poore, 2020).…”
Section: Discussionmentioning
confidence: 65%
“…In fact, the effect size of the strength of the LDG (i.e. Fisher's transformation of the correlation between species richness and absolute latitude) was −1.17, stronger than the mean effect size estimated for other marine datasets (Hillebrand, 2004a, 2004b; Kinlock et al., 2018; Menegotto et al, 2019; Rivadeneira & Poore, 2020). Further comparative studies are needed in order to make firmer conclusions regarding the generality of the departures from the idealized LDG.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Providing the dataset used is crucial for cumulative meta‐analysis (Leimu & Koricheva, 2004) and to explore the same dataset using different moderators (e.g. Menegotto et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…More precisely, they indicated that the phenomenon is non-significant in the benthic habitat. However, Menegotto et al (2019), in their comment on Kinlock et al (2018), suggest that the marine habitat categories used by them (i.e., J o u r n a l P r e -p r o o f benthic, coral reefs, coastal, open ocean) are not independent and that reclassifying the studies significantly alters one of their main results. By assigning the studies into benthic and pelagic categories, and additionally into coastal or oceanic zones, they show that non-ambiguous, evolutionarily meaningful marine habitats display a significant latitudinal decline in species richness.…”
Section: Introductionmentioning
confidence: 99%